Driven to Drink. Sin Taxes Near a Border - Timothy K.M. Beatty; Erling Røed Larsen; Dag Einar Sommervoll (Statistics Norway, Research Department, 2007)
This paper investigates household purchasing behavior in response to differing alcohol and tobacco taxes near an international border. Our study suggests that large tax differentials near borders induce economically important tax avoidance behavior that may limit a government's ability to raise revenue and potentially undermine the pursuit of important health and social policy goals. We match novel supermarket scanner and consumer expenditure data to measure the size and scope of the effect for households and stores. We find that stores near/far from the international border have statistically significantly lower/higher sales of beer and tobacco than comparable stores far/near the border. Moreover, we find that households near the border report higher consumption of these same goods. This is consistent with households facing lower prices. Finally, we find measures of externalities associated with the consumption of alcohol and tobacco are higher near the border.
Keywords: C31; F14; I18; 330; Alcohol Consumption; Tobacco Consumption; Border Trade; Taxation